A Review and Algorithm in the Diagnosis and Treatment of Sacroiliac Joint Pain - Falowski, Steven (J Pain Res, 2020)
INTRODUCTION: The sacroiliac joint (SIJ) has been estimated to contribute to pain in as much as 38% of cases of lower back pain. There are no clear diagnostic or treatment pathways. This article seeks to establish a clearer pathway and algorithm for treating patients. METHODS: The literature was reviewed in order to review the biomechanics, as well as establish the various diagnostic and treatment options. Diagnostic factors addressed include etiology, history, physical exam, and imaging studies. Treatment options reviewed include conservative measures, as well as interventional and surgical options. RESULTS: Proposed criteria for diagnosis of sacroiliac joint dysfunction can include pain in the area of the sacroiliac joint, reproducible pain with provocative maneuvers, and pain relief with a local anesthetic injection into the SIJ. Conventional non-surgical therapies such as medications, physical therapy, radiofrequency denervation, and direct SI joint injections may have some limited durability in therapeutic benefit. Surgical fixation can be by a lateral or posterior/posterior oblique approach with the literature supporting minimally invasive options for improving pain and function and maintaining a low adverse event profile. CONCLUSION: SIJ pain is felt to be an underdiagnosed and undertreated element of LBP. There is an emerging disconnect between the growing incidence of diagnosed SI pathology and underwhelming treatment efficacy of medical treatment. This has led to an increase in SI joint fixation. We have created a clearer diagnostic and treatment pathway to establish an algorithm for patients that can include conservative measures and interventional techniques once the diagnosis is identified.